Del control previo y perceptivo al posterior y preventivo: estudio de la trayectoria en el control fiscal en Colombia (1991-2019) (2020)
Colombia’s 1991 National Constituent Assembly discussed in depth the functioning of fiscal control in the new social State of law. It proposed several modifications, with moving from prior and perceptual control to subsequent and selective control as the most important one. However, twenty-eight years later, the control agencies warned about the limits of this figure and, through the legislature, the preventive control figure was created. This article analyzes this course and the transformations that this has generated in the fiscal control policy in Colombia, identifying the challenges and relevant aspects so that this figure operates without being placed above internal control.